Combined fluorescence fluctuation and spectrofluorometric measure-ments reveal a red-shifted, near-IR emissive photo-isomerized form of Cyanine 5 - Elin Sandberg; Joachim Piguet; Haichun Liu; Jerker Widengren (Royal Institute of Technology, 2022)
This folder contains all raw data underlying the results presented in a manuscript, accepted for publication in International Journal of Molecular Sciences, and entitled:

Combined fluorescence fluctuation and spectrofluorometric measurements reveal a red-shifted, near-IR emissive photo-isomerized form of Cyanine 5

Authored by:

Elin Sandberg 1, Joachim Piguet 1, Haichun Liu 1 and Jerker Widengren 1,*

1 Experimental Biomolecular Physics, Department of Applied Physics, Royal Institute of Technology (KTH), Stockholm, Sweden

*  To whom correspondence should be addressed. Email: jwideng@kth.se. Tel: +46-8-7907813

The data files are grouped into the different techniques used to generate them, and refer to the figures/tables in the manuscript where the extracted results are presented.

ABSTRACT

Cyanine fluorophores are extensively used in fluorescence spectroscopy and imaging. Upon continuous exciation, especially at excitation conditions used in single-molecule and super-resolution experiments, photo-isomerized states of cyanines easily reach population probabilies of around 50%. Still, effects of photo-isomerization are largely ignored in such experiments. Here, we studied the photo-isomerization of the pentamethine Cyanine 5 (Cy5) by two similar, yet complementary means to follow fluorophore blinking dynamics: fluorescence correlation spectroscopy (FCS) and transient state (TRAST) excitation-modulation spectroscopy. Additionally, we combined TRAST and spectrofluorimetry (spectral-TRAST), whereby emission spectra of Cy5 were recorded upon different rectangular pulse-train excitations. We also developed a framework for analyzing transitions between multiple emissive states in FCS and TRAST experiments, how the brightness of the different states is weighted, and what initial conditions that apply. Our FCS, TRAST and spectral-TRAST experiments showed significant differences in dark state relaxation amplitudes for different spectral detection ranges, which we attribute to an additional, red-shifted emissive photo-isomerized state of Cy5, not previously considered in FCS and single-molecule experiments. The photo-isomerization kinetics of this state indicate that it is formed under moderate excitation conditions, and its population and emission may thus deserve also more general consideration in fluorescence imaging and spectroscopy experiments.
Keywords: Cyanine; isomerization; FCS; TRAST; Cy5; single molecule; emission red-shift; near-IR; photo-dynamics; excitation modulation; Physical Sciences; Fysik